Time varying connectedness and volatility spillover among Shariah compliant indices - Patel, Zeenat (Department of Finance and Tax, 2025)
Shariah-compliant investing is a subset of the conventional financial market; it follows certain faith-based principles and is also seen as a subset of ESG investing. This study seeks to identify the net transmitters and receivers of volatility within the Shariah compliant equity markets of the US, Europe, Canada, Japan, the UK, Asia Pacific, and South Africa. Using several shariah-compliant Dow Jones Islamic Market (DJIM) indices as well as the shariah-compliant JSE Top 40 index, data is collected from Bloomberg for the period of 22 September 2003 to 31 March 2023. The study employs the dynamic connectedness approach to investigate time-varying interdependence and volatility spillover among the indices during periods of economic crises. The results show that during economic crises, the volatility spillover between the shariah-compliant indices decreases significantly. Therefore, we conclude that shariah compliant indices decouple from each other during economic crises. Additional results show that the DJIM US index is the dominant net transmitter of volatility, while the DJIM Japan index is the main receiver of volatility spillover within the network. This study contributes to the academic literature by including an index from the South African market, incorporating a new methodology, and finally extending the period to incorporate the Russia-Ukraine conflict. The results have implications for individual and institutional investors active in the ESG environment and for the development of shariah-compliant investing.